Study of drug utilization pattern in the department of radiotherapy in a tertiary care teaching hospital - G., Chandan N.; T., Ranganathan; H., Nagabushan (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug utilization studies are an important tool in evaluating the rationality of therapeutic practice and also it is said to improvise the therapeutic use of drugs. The present study will be undertaken to evaluate the drug utilization pattern in the department of Radiotherapy. Methods: This was a prospective, observational study that was undertaken in the department of Radiotherapy in a tertiary care teaching hospital. The study was conducted for a period of 6 months after obtaining permission from Institutional Ethical Committee. The study was conducted among cancer patients undergoing radiotherapy. The data was collected from the patient case records and was analyzed as per the WHO prescribing indicators. Results: In the present study it was observed that the average number of drugs prescribed per encounter was 7.7. The drugs prescribed by generic name were 41.4%. Percentage of encounters with an antibiotic prescribed was 100. Percentage of encounters with an injection prescribed was 20.5%. Percentage of drugs prescribed from essential drugs list was 35.8%. Conclusions: Drug utilization studies helps in modifying the prescription pattern and helps in making the drug usage more rational.